The effect of microstructure and the related bio-corrosion behavior Mg alloy in SBF artificial body fluid - Hou Jianbao; Yao Qi; Xiao Yanni; Wang Kelu; Liu Junwei (Functional Materials, 2016)
The effect of SBF artificial body fluid on microstructure and morphology characteristics of AZ91D alloy was investigated using OM, SEM and XRD. The effect of corrosion on mechanical properties also was researched. The results show that the corrosion weight loss rate initially increased, then clearly decreased, and finally remained steady. Pits began to appear when the sample was placed in a corrosive environment for five days and pitting gradually increased with longer exposure time. The pits, which made the grain boundaries indistinct, first appeared near the grain boundary area and then gradually increased in area. The main mode of corrosion is pitting and the primary corrosion product, MgOH₂, could be observed after five days of corrosion.